Juvenile sexual homicide - Myers, Wade C. (Academic Pr.)
Machine generated contents note: I -- CHAPTER 1 ORIGINS, BACKGROUND AND FRAMEWORK OF THIS BOOK -- 2 OVERVIEW OF SEXUAL HOMICIDE -- 3 THE DEVELOPMENT OF A YOUNG ADULT SADISTIC MURDERER -- PART TWO: THE STUDY -- 4 CRIMINAL ASPECTS -- 5 DSM-IV AXIS I AND RELATED DISORDERS -- 6 PERSONALITY CHARACTERISTICS AND PSYCHOPATHY -- With Roger Blashfield -- 7 THE ROLE OF ANGER AND ITS RELATIONSHIP TO SADISTIC PERSONAUTY -- DISORDER AND PSYCHOPATHY -- With Unda Monaco -- PART THREE: SPECIAL ISSUES -- 8 A TYPOLOGY OF JUVENILE SEXUAL HOMICIDE OFFENDERS -- 9 THE ELDERLY FEMALE VICTIM -- Mark E. Safarik -- 10 CONCLUDING REMARKS -- APPENDIX SUPPLEMENTARY CLINICAL INTERVIEW QUESTIONS -- AUTHOR INDEX -- SUBJECT INDEX